ANALISIS ASUHAN KEPERAWATAN DENGAN AROMATERAPI LAVENDER DAN PEPPERMINT UNTUK MENINGKATKAN KUALITAS TIDUR PADA PASIEN KANKER PAYUDARA DI RSPAD GATOT SOEBROTO - Srimpi Pamulatsih (2023)
Breast cancer is a slow-growing cancer in the breast and is usually related to hormonal, genetic, environmental and lifestyle factors. One of the effects of cancer that affects the emotions of sufferers can cause symptoms, one of which is difficulty sleeping. Sleep disturbances have been reported to affect up to 65% of breast cancer patients, occurring more frequently than patients with other oncological diseases. In breast cancer patients, insomnia is a common sleep disorder that causes a decrease in sleep quality in cancer patients. Complementary therapy that can be applied to improve sleep quality in breast cancer patients is lavender and peppermint aromatherapy. The purpose of this study was to determine the effect of lavender and peppermint aromatherapy on improving sleep quality in breast cancer patients. The number of respondents involved in this study were 2 people with 1 person given lavender aromatherapy and 1 person given peppermint aromatherapy. Data measurement used the Pitssburgh Sleep Quality Index (PSQI) sleep quality questionnaire. The results showed that there was an increase in sleep quality scores in both breast cancer patients who were given lavender and peppermint aromatherapy. Lavender and peppermint aromatherapy can improve the sleep quality of breast cancer patient